DAMPAK KEBIJAKAN TRANSPORTASI ONLINE ( STUDI KELURAHAN BUMI NYIUR KEC. WANEA KOTA MANADO ) - TELAP, ZEFANYA; DENGO, SALMIN; LALOMA, ALDEN (Sam Ratulangi University, 2019)
The purpose of this study is to determine the impact of online transportation policies,especially online motorcycle taxis in the target group (entrepreneurs / online motorcycle taxi drivers), onconventional motorcycle taxi drivers and on the user community. Based on the research results, conclusionscan be drawn: (1) Online ojek transportation policy has the expected positive impact on the target group,namely increasing online ojek driver income and helping to improve the living standards / welfare of thefamily of online ojek drivers. (2) Online ojek transportation policy also has a positive impact on the widercommunity, which makes it easy to obtain cheap, convenient, safe, and fast transportation / transportationservices. But for conventional motorcycle taxi drivers, the presence of online motorcycle taxi drivers isconsidered to be detrimental to them because income is reduced. (3) Online ojek transportation policy alsohas a positive impact on the present and future conditions of the community, whereby the community's needfor public transportation services can be more fulfilled. (4) Online ojek transportation policy has a positiveimpact on the direct costs by the community which can reduce transportation costs; and (5) Online ojektransportation policy does not affect the indirect costs that must be borne by the community as a result ofthe policy because online ojek transportation does not have a negative effect on society.Keywords: policy, the impact of online transportation policy